Comparison of incidental versus palpable thyroid nodules presenting for fine‐needle aspiration biopsy. Issue 7 (9th March 2018) - Iwata, Ayaka J.; Bhan, Arti; Lahiri, Sharon; Williams, Amy M.; Taylor, Andrew R.; Chang, Steven S.; Singer, Michael C.
Abstract: Background: Many attribute the rise in incidence of thyroid cancer to a deluge of radiologically identified incidental thyroid nodules. The clinical implications are unclear. Methods: A review was performed of all patients who underwent fine‐needle aspirations of thyroid nodules by our academic medical center's Endocrinology Division between 2006 and 2010. Medical records were reviewed to identify whether the thyroid nodule was discovered incidentally or by palpation. Results: Of 1153 patients, 37.4% underwent a biopsy because of an incidental thyroid nodule. These patients were significantly more likely to be >45 years old, men, white race, and with a body mass index >30 kg/m 2 . Of the 17.2% of incidentalomas that led to surgery, 8.5% were found to be thyroid cancer. Conclusion: Thyroid nodules discovered incidentally are increasing the diagnosis of subclinical thyroid cancers. Not investigated previously, our study found that the mode of detection was not related to malignancy or surgery.